A comparative analysis of perceptions and evaluations of Simodont® Dental Trainer: a decade of virtual simulation - Bakr, Mahmoud M.; Cameron, Andrew; Idris, Ghassan; Shamel, Mohamed; Al Ankily, Mahmoud (Frontiers in Oral Health, 2025)
Introduction/backgroundVirtual dental simulators with a haptics component have been used with great success in dental education for over a decade and is becoming an integral part of dental curricula. A large number of studies have been published about the users’ perception, acceptance and attitude towards virtual dental simulators. However, no longitudinal or long-term studies to our knowledge have been conducted to evaluate the users’ acceptance over time.Aims and objectivesThe aim of the present study is to compare the students’ and academic staff's perceptions and expectations before using the Simodont® Dental Trainer and their evaluation of the technology after using it now vs. ten years ago.Materials and methodsThe participants were invited for a trial session on the Simodont® Dental Trainer and were asked to evaluate different aspects of this virtual simulator by completing a pre-experimental and post-experimental questionnaire. The data collected from the current study was compared against similar data collected and published a decade ago in the same educational institution.ResultsIn general, participants from the present study rated different aspects of Simodont® dental trainer higher than their counterparts from the previous study a decade ago. Students from the present study were more excited and more likely to accept the technology when compared to the academic staff members as well as their counterparts from the 2014 student cohort. Academic staff and students from both studies were in total agreement that the Simodont® dental trainer should not be replacing traditional teaching. Both cohorts agreed that the feedback provided by the simulator should be supplemented by feedback from human supervisors. The open-ended responses highlighted the cost-effectiveness, student engagement, value of accessibility and flexibility in virtual dental training as well as persistent technical issues within the software as well as the need to develop more didactic content alongside the practical tasks offered by the simulator.ConclusionGenerational differences as well as technology limitations affect the perception to virtual dental simulation. The acceptance of the Simodont® dental trainer is following the cycle of technology adoption models.